PRAGMATIC ITEMS FUNCTIONS IN RUSSIAN EVERYDAY SPEECH OF DIFFERENT SOCIAL GROUPS - Наталья Викторовна Богданова-Бегларян (Natalya V. Bogdanova-Beglaryan) (Vestnik Permskogo universiteta: Rossijskaâ i zarubežnaâ filologiâ, 2017)
The article deals with the description of results of everyday speech analysis (social dialects of a modern city). The object of the investigation is pragmatic items functions in spontaneous speech (communication) and disquisition of their importance as of a social dialect marker. The research has been done on the basis of corpora materials (the Corpus of Spoken Russian Language, module “One Speaker’s Day”). There are three data blocks: the whole sub-corpus analysis (12 speakers), the analysis of three age groups, and the analysis of two gender groups.